An investigation of the rotor wake characteristics of an axial flow compressor with clean and distorted inlet flows - Maksoud, T. M. A. (Cranfield University, 1983)
Three-dimensional velocity components and six stress tensor components have been obtained experimentally inside the rotor wake of an axial flow compressor. The measurements were made using a Hot-wire assembly with a micro-electronic closed system. Measurements were taken in a clean flow and in a flow with imposed inlet sine wave pressure distortion. The set of wake data in the distortion flow mode , presented this thesis , are probably the first reported comprehensive measurements taken to discern the effect of inlet sine wave pressure distortion on rotor wake behavior. The mechanism by which the loading variation affects the wake characteristics radially, frcm the hub to the tip, has been studied. A suite of rotor wake analysis programs has been developed. The suite includes programs dealing with self-similarity and preservation , decay and width variation , flow thicknesses and harmonic decomposition of the rotor wake. A mathematical model for the , wake width/decay characteristics based on preceeding work has been improved. The model uses the integeral manentum technigpe. The improvements allow the inclusion of pressure terms , turbulence terms and the radial flow outside the wake edge in the final solution.